Chemotherapeutic and targeted drugs-induced immunogenic cell death in cancer models and antitumor therapy: An update review - Zhai, Jiaqi; Gu, Xi; Liu, Yang; Hu, Yueting; Jiang, Yi; Zhang, Zhenyong (Frontiers in Pharmacology, 2023)
As traditional strategies for cancer treatment, some chemotherapy agents, such as doxorubicin, oxaliplatin, cyclophosphamide, bortezomib, and paclitaxel exert their anti-tumor effects by inducing immunogenic cell death (ICD) of tumor cells. ICD induces anti-tumor immunity through release of, or exposure to, damage-related molecular patterns (DAMPs), including high mobility group box 1, calreticulin, adenosine triphosphate, and heat shock proteins. This leads to activation of tumor-specific immune responses, which can act in combination with the direct killing functions of chemotherapy drugs on cancer cells to further improve their curative effects. In this review, we highlight the molecular mechanisms underlying ICD, including those of several chemotherapeutic drugs in inducing DAMPs exposed during ICD to activate the immune system, as well as discussing the prospects for application and potential role of ICD in cancer immunotherapy, with the aim of providing valuable inspiration for future development of chemoimmunotherapy.